Improvement of transportation of melon crops using increased loading standards - Tursunkhodjaeva Rashida; Marek Milosz; Saidivaliev Shukhrat; Tashmatova Mukaddas (BIO Web of Conferences)
In this paper, the economic efficiency of introducing an increased rate of loading into wagons during the transportation of melons is considered. The relevance of the topic is due to the need to optimize logistics processes and reduce the cost of transporting agricultural products. The study analyzes the current loading standards and their impact on the cost of transportation, as well as assesses the potential benefits of increasing standards. Various factors are considered, such as the possibility of increasing the volume of transported products, reducing transportation costs per unit of goods, and improving trade turnover. The research methodology includes a comparative analysis of existing practices, statistical data on the transportation of melons, and economic modeling. As a result, it was found that the introduction of an increased loading rate can lead to significant cost savings, increase profitability, and improve the competitiveness of agricultural products on the market.